2017
DOI: 10.3892/ol.2017.6510
|View full text |Cite
|
Sign up to set email alerts
|

Primary lymphoepithelioma-like carcinoma of the lung: An unusual cancer and clinical outcomes of 14 patients

Abstract: Abstract. Advanced lung cancer is considered to exhibit a poor prognosis; however, the pulmonary lymphoepithelioma-like carcinoma (LELC), a rare subtype of non-small cell lung cancer (NSCLC), exhibits an improved prognosis, compared with non-LELC. The present study aimed at investigating the clinical manifestation, imaging characteristics, pathology, tumor markers, treatment and prognosis of primary LELC of the lung. A total of 14 patients with pulmonary LELC were confirmed by surgery and pathology. Clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…15 There is no sex predilection in most of the studied populations. 2,11,12,[14][15][16] The age at diagnosis usually ranges from 35 to 85 years, 1,2,10,12,13,17 with the mean/median age between 51 and 57 years. 2,10,12,13,17 Overall, patients with pulmonary LELC have been found to be younger than those with other NSCLCs.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…15 There is no sex predilection in most of the studied populations. 2,11,12,[14][15][16] The age at diagnosis usually ranges from 35 to 85 years, 1,2,10,12,13,17 with the mean/median age between 51 and 57 years. 2,10,12,13,17 Overall, patients with pulmonary LELC have been found to be younger than those with other NSCLCs.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…ALK alteration was detected positive in three PLELC patients in our study, while only one was reported in the literature by Ose et al 38 The variant rates may be due to the small sample size of each study which warrants further investigation. In the study by Gou and Wu which demonstrated the frequencies of driver mutations in nonsmall cell lung cancer in China, 19 the mutation rates of EGFR were 48.4% (675/1795), 4.3% (9/208), and 28.2% (570/2021) in lung adenocarcinoma, squamous cell cancer 36 Hong Kong, China 11 NA 0 NA NA Liang et al 8 Guangzhou, China 52 0/11 NA NA NA Liu et al 29 Guangzhou, China 32 0 NA NA NA Wang et al 28 Guangzhou, China 42 1 0 NA NA Fang et al 37 Guangzhou, China 113 2 0 NA NA Chang et al 30 Tai Wan, China 66 8 0 0 0 (BRAF) Ose et al 38 Osaka, Japan 1 0 1 NA NA Hong et al 31 Guangzhou, China 91 0 0 NA 14 (P53) Lin et al 39 Guangzhou, China 39 0/19 NA NA NA Lin et al 40 Fuzhou, China 20 0/3 0/2 0/1 NA Xie et al 10 Guangzhou, China 429 2 0 0 NA Zhou et al 41 Guangzhou, China 27 0 0 1 7 (P53) Yin et al 42 Guangzhou 43 An et al reported that the mutation rate of driver genes might differ among different histology subtypes and smoking status. 44 EGFR and ALK alteration is rare in PLELC.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary lymphoepithelioma-like carcinoma (LELC) is a rare subtype of non-small cell lung cancer (NSCLC), accounting for < 1% of all histologic type of lung cancers. So far only ∼600 cases have been reported in the English-language literature (1)(2)(3)(4)(5)(6)(7). Histologically, the disease is characterized by epithelial tumor cells nests surrounded or infiltrated by numerous lymphocytes (1) ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the experience on nasopharyngeal cancer, the potential diagnostic, prognostic and predictive role of plasma EBV-DNA copy number in pulmonary LELC triggered much interest. Because of the rarity of pulmonary LELC, previous studies usually focused on small, heterogeneous cohorts with different tumor stage and inconsistent treatments (2)(3)(4). There lacks a universally accepted threshold of EBV-DNA copy number suggesting immediate disease progression for the patients after radical treatment.…”
Section: Introductionmentioning
confidence: 99%